2007
DOI: 10.1158/1535-7163.mct-06-0788
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol induces apoptosis in glioblastoma cells through oxidative stress

Abstract: Despite recent advances in understanding molecular mechanisms involved in glioblastoma progression, the prognosis of the most malignant brain tumor continues to be dismal. Because the flavonoid kaempferol is known to suppress growth of a number of human malignancies, we investigated the effect of kaempferol on human glioblastoma cells. Kaempferol induced apoptosis in glioma cells by elevating intracellular oxidative stress. Heightened oxidative stress was characterized by an increased generation of reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
181
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(190 citation statements)
references
References 45 publications
6
181
0
3
Order By: Relevance
“…In addition to GSH, catalase and SOD play important role to detoxify hydrogen peroxide and super-oxides, respectively. A number of therapeutic agents have been shown to increase intracellular ROS generation by downregulating antioxidant enzymes such as catalase and SOD (7,20,23). However, some other studies have reported that reduction in intracellular GSH is necessary for the formation of ROS (10,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to GSH, catalase and SOD play important role to detoxify hydrogen peroxide and super-oxides, respectively. A number of therapeutic agents have been shown to increase intracellular ROS generation by downregulating antioxidant enzymes such as catalase and SOD (7,20,23). However, some other studies have reported that reduction in intracellular GSH is necessary for the formation of ROS (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…ROS are produced by eukaryotic cells during normal oxidative metabolism and cells' antioxidant system scavenges ROS to maintain the redox balance. However, an imbalance between production of ROS and cells antioxidant system's ability to readily detoxify ROS results in oxidative stress (6,7). Glutathione (GSH) is the most abundant intracellular antioxidant involved in the protection of cells against oxidative damage and in various detoxification mechanisms (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…In response to ROS, mitochondrial membrane become permeable leading to the release of cytochrome c which induces caspases cascades ultimately resulting in apoptosis (Conklin 2004;Circu and Aw 2010;Simon et al 2000;Thayyullathil et al 2008). Sharma et al (2007) reported that Kaempferol showed apoptogenic activity in human glioblastoma cells by elevating the levels of ROS. Ellagic acid caused apoptosis of tsgh8301 human bladder cancer cells (Ho et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Kaempferol, is a member of the flavonoid family and exhibits potential anti-tumor activities. Previous studies demons -trated that kaempferol inhibits growth and proliferation of cancer cells by various mechanisms including apoptosis (Sharma et al, 2007) cell cycle arrest (Cho et al, 2013) and inhibition of tyrosine phosphorylation (Lee et al, 1998). However, studies focusing on the potential of kaempferol in overcoming invasiveness of cancer cells particularly lung cancer have rarely been done.…”
Section: Discussionmentioning
confidence: 99%